Identification of potent farnesoid X receptor (FXR) antagonist showing favorable PK profile and distribution toward target tissues: Comprehensive understanding of structure-activity relationship of FXR antagonists. Issue 11 (1st June 2019) - Teno, Naoki; Yamashita, Yukiko; Masuda, Arisa; Iguchi, Yusuke; Oda, Keisuke; Fujimori, Ko; Hiramoto, Takie; Nishimaki-Mogami, Tomoko; Une, Mizuho; Gohda, Keigo
Graphical abstract: Abstract: Antagonizing transcriptional activity of farnesoid X receptor (FXR) in the intestine has been reported as an effective means for the treatment of nonalcoholic fatty liver disease, type 2 diabetes and obesity. We describe herein that the building blocks necessary to maintain the antagonism of our chemotype were investigated in order to modulate in vivo pharmacokinetic behavior and the tissue distribution without blunting the activity against FXR. A comprehensive understanding of the structure-activity relationship led to analog30, which is superior to12 in terms of its pharmacokinetic profiles by oral administration and its tissue distribution toward target tissues (liver and ileum) in rats while preserving the in vitro activity of12 against FXR. Thus, 30 should be a candidate compound to investigate the effects of inhibiting FXR activity while simultaneously improving the outcome of nonalcoholic fatty liver disease, type 2 diabetes and obesity.